MODE OF ATTACHMENT OF QUADRIACANTHUS SPP. (MONOGENEA: DACTYLOGYRIDAE) TO THE GILLS OF THE NILE CATFISH CLARIAS GARIEPINUS AND THEIR LOCAL HISTOPATHOLOGICAL IMPACTS - M.I. Mashaly (Zenodo, 2019)
This is the first study on the mode of attachment and histopathological impacts of the monogeneans Quadriacanthus species. Most adult worms attach their haptor between two adjacent gill lamellae, others to the gill filaments (primary gill lamellae) particularly in the interlamellar spaces and a few attach to the top (distal) region of the gill lamella (secondary gill lamella). In all cases, hamuli, dorsal and ventral bars and marginal hooklets share in securing attachment. The posterior glandular system of Quadriacanthus spp. may play a significant role in attachment. Local histopathological changes of Quadriacanthus spp. include, compression of the gill lamellae, degeneration and rupture of the outermost pavement cells, breakdown of the wall of the blood spaces, fibrosis, necrosis, reduction and desquamation of the lamellar epithelial layers, loss of the innermost pavement cells, swelling and rupture of the blood cells and swelling and vaculation of the lamellar tissues at the site of hook insertion. The local host responses include proliferation of undifferentiated epithelial cells into M1 and M2 mucous cells, hyperplasia and appearance of lymphocytes at the site of haptor attachment. : {"references": ["Amatyakul, C. (1972). Parasites of pond-raised Clarias in Thailand. FAO Aquaculture Bulletin, 5, 16-17.", "Arafa, S. Z., El-Naggar, M. M., & Kearn, G.C. (2003). Scanning electron microscope observations on the monogenean skin parasite Macrogyrodactylus congolensis [Prudhoe, 1957] Yamaguti, 1963. Acta Parasitologica, 48(3):163-171", "Arafa, S. Z., El-Naggar, M.M., & El-Abbassy, S.A. (2009). Mode of attachment and histopathological effects of Macrogyrodactylus clarii, a monogenean gill parasite of the catfish Clarias gariepinus, with a report on host response. Acta Parasitologica, 54(2), 103-112.", "Bishai, H.M., & Khalil, M.T. (1997). Freshwater fishes of Egypt: Egyptian Environmental Affairs Agency. pp.577.", "Camargo, M.M., & Martinez, C.B. (2007). Histopathology of gills, kidney and liver of a Neotropical fish caged in an urban stream. Neotropical Ichthyology, 5(3), 327-336.", "Cone, D., & Odense, P. (1984). Pathology of five species of Gyrodactylus Nordmann, 1832 (Monogenea). Canadian Journal of Zoology, 62(6), 1084-1088.", "El-Naggar, M. M., Hagras, A. E., Ogawa, K., Hussein, A. B., & El-Naggar, A. M., (2001). Attachement of Cichlidogyrus monogenean species to the gills of the Nile fish Oreochromis niloticus and their local pathological impact on them. Journal of Egyptian German Society of Zoology, 35(D), 143-156.", "El-Naggar, M. M., & Kearn, G. C., (1989). Haptor glands in the gill-parasitic, ancyrocephaline monogenean Cichlidogyrus halli typicus and the report of a possible prokaryotic symbiont. International Journal for Parasitology, 19(4), 401-408.", "El-Naggar, M.M., & Serag, H.M., (1985). The monogenean Quadriacanthus kearni n. sp. and a report of Q. clariadis clariadis Paperna, 1979 on the gills of Clarias lazera in Nile Delta. Journal of the Egyptian Society of Parasitology, 15(2), 479-492.", "El-Naggar, M.M., & Serag, H. M. (1986). Quadriacanthus aegypticus n. sp., a monogenean gill parasite from the Egyptian teleost Clarias lazera. Systematic Parasitology, 8(2), 129-140.", "El-Naggar, M.M., Cable, J., Arafa, S. Z., El-Abbassy, S. A., & Kearn, G. C. (2016). Scanning and transmission electron microscopy of the histopathological impact of Macrogyrodactylus clarii (Monogenea: Gyrodactylidae) on the gills of catfish, Clarias gariepinus. Folia Parasitologica, 63(017). doi: 10.14411/fp.2016.017", "Evans, D.L., & Gratzek, J.B. (1989). Immune defense mechanisms in fish to protozoan and helminth infections. American Zoologist, 29(2), 409-418.", "Francov\u00e1, K., S if v\u00e1, M., Bla\u017eek, R., Gelnar, M., Mahmoud, Z.N., & \u0158 h lk v\u00e1, E. (2017). Quadriacanthus species (Monogenea: Dactylogyridae) from catfishes (Teleostei: Siluriformes) in eastern Africa: new species, new records and first insights into interspecific genetic relationships. Parasites and Vectors, 10(1), 361. DOI 10.1186/s13071-017-2223-4", "Harris, P. (1983). The morphology and life-cycle of the oviparous O\u00f6gyrodactylus farlowellae gen. et sp. nov. (Monogenea, Gyrodactylidea). Parasitology, 87(3), 405-420.", "Hirazawa, N., Ishizuka, R., & Hagiwara, H. (2016). The effects of Neobenedenia girellae (Monogenea) infection on host amberjack Seriola dumerili (Carangidae): Hematological and histopathological analyses. Aquaculture, 461, 32-39.", "Lester, R. (1972). Attachment of Gyrodactylus to Gasterosteus and host response. Journal of Parasitology, 58(4),717-722.", "Mansell, B., Powell, M., Ernst, I., & Nowak, B. F. (2005). Effects of the gill monogenean Zeuxapta seriolae (Meserve, 1938) and treatment with hydrogen peroxide on pathophysiology of kingfish, Seriola lalandi Valenciennes, 1833. Journal of Fish Diseases, 28(5), 253-262.", "Moln\u00e1r, K. (1972). Studies on gill parasitosis of the grasscarp (Ctenopharyngodon idella) caused by Dactylogyrus lamellatus Achmerov, 1952. IV. Histopathological changes. Acta Veterinaria Academiae Scientiarum Hungaricae, 22(1), 9-24.", "Pahor-Filho, E., Castillo, A.S.C., Pereira, N. L., Pilarski, F., & Urbinati, E.C. (2017). Levamisole enhances the innate immune response and prevents increased cortisol levels in stressed pacu (Piaractus mesopotamicus). Fish and Shellfish Immunology, 65, 96-102.", "Paperna, I. (1980). Parasites infections and diseases of fish in Africa. FAO. CIFA Technical paper, 7, 7-23.", "Piasecki, W., Goodwin, A.E., Eiras, J.C., & Nowak, B.F. (2004). Importance of Copepoda in freshwater aquaculture. Zoological Studies, 43(2), 193-205.", "Ramadan, N., El-Banhawy, M., & Abdel Salam, M. (1995). Parasitological investigation on two monogenetic trematodes and their pathological impact on the grass", "Rosety, I., Ribelles, A., & Carrasco, C. (2002). Morpho-histochemical changes in the gills of turbot, Scophthalmus maximus L., induced by sodium dodecyl sulfate. Ecotoxicology and Environmental Safety, 51(3), 223-228.", "Schwaiger, J., Ferling, H., Mallow, U., Wintermayr, H., & Negele, R. (2004). Toxic effects of the non-steroidal anti-inflammatory drug diclofenac: Part I: histopathological alterations and bioaccumulation in rainbow trout. Aquatic Toxicology, 68(2), 141-150.", "Trujillo-Gonz\u00e1lez, A., Constantinoiu, C.C., Rowe, R., & Hutson, K.S. (2015). Tracking transparent monogenean parasites on fish from infection to maturity. International Journal for Parasitology: Parasites and Wildlife, 4(3), 316-322.", "Wilson, J.M., & Laurent, P. (2002). Fish gill morphology: inside out. Journal of Experimental Zoology, 293(3), 192-213.", "Zhao, X., Findly, R.C., & Dickerson, H.W. (2008). Cutaneous antibody-secreting cells and B cells in a teleost fish. Developmental and Comparative Immunology, 32(5), 500-508."]}